2021
DOI: 10.1101/2021.04.28.21256253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the Factor Structure of the DSM-5 Level 1 Cross-Cutting Symptom Measure

Abstract: The DSM-5 Level 1 Cross-Cutting Symptom Measure (DSM-XC) is a transdiagnostic mental health symptom measure that has shown promise in informing clinical diagnostic evaluations and as a screening tool for research. However, few studies have assessed the latent dimensionality of the DSM-XC or provided guidance on how to score the survey. In this report, we examined the factor structure of the DSM-XC in a sample of over 3500 participants enrolled in a protocol on the mental health impact of COVID-19 conducted thr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…This measure is one of the core common data elements that NIMH researchers are expected to collect. 19 Using data from all enrolled study participants, we performed a series of exploratory and confirmatory factor analyses and identified a six-factor solution which was robust across age, sex, and calendar time (see https://doi.org/10.1101/2021.04.28.21256253 20 ). Each factor captured symptoms related to a general construct of psychopathology, which we provisionally termed: mood, worry, activation, somatic, thoughts, and substance use.…”
Section: Distressmentioning
confidence: 99%
“…This measure is one of the core common data elements that NIMH researchers are expected to collect. 19 Using data from all enrolled study participants, we performed a series of exploratory and confirmatory factor analyses and identified a six-factor solution which was robust across age, sex, and calendar time (see https://doi.org/10.1101/2021.04.28.21256253 20 ). Each factor captured symptoms related to a general construct of psychopathology, which we provisionally termed: mood, worry, activation, somatic, thoughts, and substance use.…”
Section: Distressmentioning
confidence: 99%
“…The CCSM consists of 23 items scored on a 5‐point Likert scale (‘ not at all ’ to ‘ nearly every day ’) that assess individuals' experiences of mental health symptoms over the past 2 weeks across 13 psychiatric domains including depression, anger, mania, anxiety, somatic symptoms, suicidal ideation, psychosis, sleep problems, memory, repetitive thoughts and behaviours, dissociation, personality functioning and substance use (Cronbach's α = 0.90). Previous factor analytic studies have suggested that the CCSM items can be organised into a bi‐factor structure with a general psychopathology factor and two specific factors (internalising and thought disorders) (Gibbons et al, 2021). Alternatively, it has also been suggested that a two‐factor or six‐factor model without a p factor would fit well (Gibbons et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Previous factor analytic studies have suggested that the CCSM items can be organised into a bi-factor structure with a general psychopathology factor and two specific factors (internalising and thought disorders) (Gibbons et al, 2021). Alternatively, it has also been suggested that a two-factor or six-factor model without a p factor would fit well (Gibbons et al, 2021). In the present study, only 12 of the 13 domains were measured as substance use was measured separately using the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) (Humeniuk et al, 2008).…”
Section: Psychopathologymentioning
confidence: 99%
“…The current study’s findings in Figure 1 reported an excellent model fit for CAM. Thus, CAM is a valid instrument to measure criminal thinking as it fulfills both criteria (EFA and CFA) suggested by researchers (Gibbons et al , 2021; Lace and Merz, 2020) to ensure the construct validity of the instrument. Furthermore, indices (e.g.…”
Section: Structural Validation Of Criminal Attitude Measurementioning
confidence: 99%